Repurposing an old drug: aztreonam as a new treatment strategy for gonorrhoea. (30th January 2017) - Davido, Benjamin; Dinh, Aurelien; Senard, Olivia; Calin, Ruxandra; Makhloufi, Sabrina; Salomon, Jerome
Abstract : Objectives: To determine whether aztreonam is still an effective drug for the treatment of gonorrhoea. Methods: Observational study of patients with gonorrhoea diagnosed by urine multiplex PCR, with a past medical history of allergy to β-lactams or relapse after treatment with a third-generation cephalosporin. Patients received a single 1 g dose of aztreonam in accordance with the manufacturer's instructions. Results: Five patients (four males, one female) were enrolled, comprising two who were allergic to β-lactams and three previously treated with cephalosporins who relapsed. Median age was 38 years (range 23–51). Following treatment with aztreonam all were cured without any adverse event. All the men were free of symptoms, and the woman tested negative for gonorrhoea 1 month after treatment. Conclusion: Aztreonam appears to be an effective alternative to cephalosporins in the treatment of uncomplicated gonorrhoea, particularly when patients are suspected of being infected by strains with reduced susceptibility to ceftriaxone or are known to be allergic to penicillin.